2021
DOI: 10.1097/yic.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of celecoxib augmentation of antidepressant or anxiolytic treatment on affective symptoms and inflammatory markers in patients with anxiety disorders: exploratory study

Abstract: Prolonged stress has been associated with elevated levels of circulating proinflammatory cytokines. Cyclo-oxygenase-2 inhibitors such as celecoxib exert anti-inflammatory effects and may enhance the response to antidepressant drug treatment in patients with depressive disorders, but their effect on anxiety symptoms in patients with anxiety disorders is uncertain. Patients with a primary diagnosis of an anxiety disorder, with stabilised symptoms, underwent either 6 weeks of celecoxib augmentation of continued t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…A meta-analysis of randomized clinical trials reported celecoxib to decrease depressive symptoms with reduced adverse effects; however, the mean estimate was claimed to be uncertain due to a high risk of bias and heterogeneity [ 71 ]. An exploratory study revealed that celecoxib augmentation of anxiolytic or antidepressant drugs exhibits positive effects on anxiety, depression, and mental well-being [ 72 ]. In contrast to these findings, recently published data of a placebo-controlled, double-blind, randomized trial reported that celecoxib augmentation of vortioxetine has no evidence of superior efficacy as compared to a placebo in mitigating depressive severity [ 73 ].…”
Section: The Quest Of Repurposing and Efforts From Medicinal Chemistsmentioning
confidence: 99%
“…A meta-analysis of randomized clinical trials reported celecoxib to decrease depressive symptoms with reduced adverse effects; however, the mean estimate was claimed to be uncertain due to a high risk of bias and heterogeneity [ 71 ]. An exploratory study revealed that celecoxib augmentation of anxiolytic or antidepressant drugs exhibits positive effects on anxiety, depression, and mental well-being [ 72 ]. In contrast to these findings, recently published data of a placebo-controlled, double-blind, randomized trial reported that celecoxib augmentation of vortioxetine has no evidence of superior efficacy as compared to a placebo in mitigating depressive severity [ 73 ].…”
Section: The Quest Of Repurposing and Efforts From Medicinal Chemistsmentioning
confidence: 99%
“…Cyclo-oxygen-ase-2 (COX-2) can regulate the occurrence and development of depression. In recent years, COX-2 inhibitors have been widely used in the treatment of depressed patients, and the drugs commonly used in clinical practice as COX-2 inhibitors are non-steroidal anti-inflammatory drugs (NSAIDs), all of which have varying degrees of efficacy in depression (111)(112)(113). Some natural compounds such 10.3389/fpsyt.2022.1037588 as xanthines, alkaloids, astragals, flavonoids, terpenoids and quinones also have the ability to inhibit COX-2 activity.…”
Section: Cyclo-oxygen-ase-2 Inhibitorsmentioning
confidence: 99%
“…Inflammatory biomarkers are an interesting area of investigation, given the known involvement of inflammation factors in the pathophysiology of depression [ 44 ], and a number of possible biomarkers are currently under investigation for diagnosis, outcome prediction, staging, and stratification of interventions [ 45 - 48 ]. However, at present there are no approved inflammatory biomarkers for use in routine clinical practice.…”
Section: Biomarkers In Major Depressive Disordersmentioning
confidence: 99%